2021
DOI: 10.1155/2021/9912686
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation of Microglia Function and Phenotypes in Neurodegenerative Diseases

Abstract: Microglia-mediated neuroinflammation is one of the most remarkable hallmarks of neurodegenerative diseases (NDDs), including AD, PD, and ALS. Accumulating evidence indicates that microglia play both neuroprotective and detrimental roles in the onset and progression of NDDs. Yet, the specific mechanisms of action surrounding microglia are not clear. Modulation of microglia function and phenotypes appears to be a potential strategy to reverse NDDs. Until recently, research into the epigenetic mechanisms of disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 167 publications
(197 reference statements)
0
7
0
Order By: Relevance
“…In response to injury in the brain, neuroinflammation occurs in various cells, including neurons, microglia and astrocytes ( 62 ). In the acute phase, the damaged neurons and resident immune cells secrete inflammatory mediators and activate microglia, which are the first line of defense in the nervous system ( 63 ) that produce more inflammatory factors ( 62 , 64 ). Additionally, astrocytes that are activated by ischemia mediate inflammatory response to aggravate ischemic injury.…”
Section: Nlrp3 Inflammasome-mediated Neuroinflammation In Ischemic St...mentioning
confidence: 99%
“…In response to injury in the brain, neuroinflammation occurs in various cells, including neurons, microglia and astrocytes ( 62 ). In the acute phase, the damaged neurons and resident immune cells secrete inflammatory mediators and activate microglia, which are the first line of defense in the nervous system ( 63 ) that produce more inflammatory factors ( 62 , 64 ). Additionally, astrocytes that are activated by ischemia mediate inflammatory response to aggravate ischemic injury.…”
Section: Nlrp3 Inflammasome-mediated Neuroinflammation In Ischemic St...mentioning
confidence: 99%
“…Therefore, a reduction in the quantity of orexins could lead to an increase in microglial dysfunction with a consequent increase in the probability of developing neurodegenerative diseases [66]. As mentioned, the orexin systems play a pivotal role in neuroprotection and neuroinflammation [67,68]. OXA and OXB regulate the homeostatic mechanisms of energy balance and metabolism [64] through the activation of two G proteins (OX1, OX2) coupled to receptors, OX1R and OX2R, respectively [68].…”
Section: Orexin In Microglia Activationmentioning
confidence: 99%
“…As mentioned, the orexin systems play a pivotal role in neuroprotection and neuroinflammation [67,68]. OXA and OXB regulate the homeostatic mechanisms of energy balance and metabolism [64] through the activation of two G proteins (OX1, OX2) coupled to receptors, OX1R and OX2R, respectively [68]. Recent studies in neuronal cell cultures have shown that orexin plays a role in neuroprotection [64,65] by reducing lipid peroxidation, apoptosis and neuronal inflammation [39,[69][70][71].…”
Section: Orexin In Microglia Activationmentioning
confidence: 99%
“…Interestingly, maternal TPPU maintained low levels of Trem2 in both 5XFAD and WT mice. Microglia plasticity is modulated by epigenetic modifications including DNA methylation and histone acetylation reported here [ 57 , 58 ]. Therefore, we may speculate that microglia were imprinted early by epigenetic changes induced by TPPU treatment to a neuroprotective phenotype, although further investigations would be required to confirm the involvement of either HDACs inhibition or specific DNA gene methylation changes.…”
Section: Discussionmentioning
confidence: 99%